In search of rationality : business students on family-owned firms - Koczerga, Maciej (Economics and Business Review, 2013)
The objective of this paper is to explore the attitudes of business students towards family firms and family entrepreneurship. The culture of Poland is profoundly family-oriented and entrepreneurship is found more and more as an attractive career path in society. These factors might indicate that this environment may be particularly fertile for family-owned firm development. Business students though display reluctance towards family firms and family entrepreneurship. The research method applied in this study is focus group interviews, as qualitative data provide particularly rich information and grounds for conclusions. This study also implies the need for inclusion of family enterprise issues in business education, as well as developing skills essential for working in such an environment. (original abstract)